Health problem resulting from the use of e - cigarettes - Barbara Maziarz; Magdalena Makarewicz; Magdalena Kubicka; Katarzyna Łapa; Barbara Nieradko-Iwanicka (Kazimierz Wielki University, 2020)
Introduction: Electric smoking devices called e-cigarettes are gaining more and more popularity nowadays and vaping  is becoming more and more fashionable. However their use contributes to the emergence of new health  problems like lipoid pneumonia associated with vaporization. Purpose: The purpose of the work is to analyze the advantages and disadvantages of e-cigarettes and to assess the risk of their use compared to traditional forms of smoking. Method: The article is a review of recent publicatopns available in the PubMed database.  It was searched on January 20th 2020 with key words 'e-cigarettes', 'vaping', 'health problems'. After analyzing several dozen abstracts, 18 full-text publications were selected for review. Summary: In conclusion: vaping carries the risk of thermal injury and  chemical burns caused by damage of the device, it leads to an increase in the number of vaping- addicted youth, and can also cause shortness of breath, chest pain, cough, hemoptysis, nausea, vomiting, diarrhea, abdominal pain, chills, weight loss, fatigue , malaise, headache, fever, tachycardia, tachypnoe, hypoxemia,  low white blood cel count, lipoid pneumonia and pneumothorax in users.